ASSESSMENT OF THE WILLINGNESS TO PAY FOR HIV SELF-TESTING SERVICES AMONG STUDENTS OF THE UNIVERSITY OF CROSS RIVER STATE. - N.M. ABASUMOH; L.P. ASUQUO (African Journal of Health, Safety and Environment, 2026)
The study assessed the willingness to pay for HIV self-testing (HIVST) services among students of the University of Cross River State, Nigeria. The need to expand HIV testing coverage among young people, coupled with continuous barriers associated with facility-based testing such as lack of confidentiality, stigma, and inconvenience, necessitates the exploration of alternative testing strategies. HIV self-testing gives a private and user-controlled approach, and its sustainability relies mostly on the willingness of users to pay. The study adopted a descriptive cross-sectional survey design with a total of 300 valid responses analyzed out of the 308 retrieved questionnaires, representing a 96.3% response rate after data cleaning. Descriptive statistics such as frequencies and percentages were used in data analysis. The findings reported that those willing to purchase HIV self-testing kits at ₦1,200 were 74.7% of the respondents, while 85.7% were willing to use HIVST in the future. Respondents expressed that reduced risk of status disclosure, increased confidentiality, knowledge of HIV status, convenience, and autonomy are key motivating factors. They also highlighted concerns about test accuracy, perceived cost, psychological risks such as self-harm, and preference for free facility-based testing services as barriers to uptake. The study revealed high acceptability of HIV self-testing among university students and identified affordability and perceived reliability as important determinants of willingness to pay. The study therefore recommends subsidization of HIVST kits, strengthened awareness campaigns, and integration of counseling and linkage to care services to enhance adoption and sustainability.